SystemC-WMS: wave mixed signal simulator for non-linear heterogeneous systems. (1st January 2014) - Biagetti, Giorgio; Giammarini, Marco; Ballicchia, Mauro; Conti, Massimo; Orcioni, Simone
The present paper proposes a methodology for extending SystemC to mixed signal heterogeneous systems. To that end, a method for modelling analogue modules using wave quantities is proposed, and a new kind of port and channel were defined. This class library is plugged directly on top of the standard SystemC kernel, so as to allow a seamless integration with the pre-existing simulation environment, and is designed to permit total interconnection freedom between analogue modules to ease the development of reusable analogue libraries. Moreover, this allows for a uniform treatment of heterogeneous domains. To highlight all these aspects a buck-converter with digital control and an induction motor were simulated.